ANALYSIS OF VIBRATION AND OSCILLATION SOURCES OF MACHINE-TRACTOR AGGREGATES UNITS - Галич, І. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2019)
With the increasing speed of machine-tractor aggregates, the energy intensity of tractors and labor productivity increases. In turn, this leads to an increase in the dynamic loading of nodes and components of machine-tractor aggregates, an increase in the level of oscillation and the emergence of dynamic and vibrational loads, which negatively affects both the node and components of the tractor or the aggregate, and the implementation of agrotechnical requirements. An analysis of recent studies and publications has shown that the introduction of energy-intensive technology into agricultural production leads to a decrease in soil fertility due to spraying and re-compression by engines, which aggravate agro-ecological indicators. In the study, the analysis of sources of vibrations and oscillations of elements of machine-tractor aggregates is presented. The frequency of influence on machine-tractor aggregates of various agrofones at different speeds of motion is analyzed. Experimental studies have determined the spectral density of the hook effort of the tractor during cultivating on disk field and steam. The results of experimental studies of the active damping system are presented. The result of the study is the suggestion to reduce the oscillations of the tractor and agricultural machine to justify comprehensive measures that prevent deterioration of the conditions of the unit. Fluctuations of the tractor, caused by sources of excitations, lead to deterioration of the performance of agrotechnical requirements due to the non-straightforwardness of the trajectory of motion, redevelopment of soil. To reduce the vibrations of the tractor and the agricultural machine it is necessary to substantiate the complex measures that prevent deterioration of the conditions of the unit